Best practice, best model, best fit: Strategic configurations for the institutionalization of corporate real estate management in Europe. Issue 2 (2014) - ,; ,
Abstract : Purpose – The purpose of this study is to team broadly accepted general management frameworks with the specific situation of corporate real estate and suggest a holistic configurations framework for CREM that takes into account the highly diverse context parameters.Design/methodology/approach – Based on general management frameworks and research on CREM issues, a CRE management framework – the "CREM map" – is suggested that guides a study on which parameters drive CREM and how they are integrated. A qualitative approach is used that collects data from large European corporates. The analyses are performed through computer‐assisted qualitative data analysis.Findings – Multiple parameters form heterogeneous context constellations that make it necessary to individually configure a CREM system. While some "general principles" regarding CREM targets, strategy, organization, and controlling systems and their relationships can be identified as "best practices", the key finding is that a holistic concept for CREM needs to be guided by "best fit" considerations, resulting in at least several, context‐specific designs of CREM.Practical implications – The CREM‐map and CREM principles provide orientation in the process of design, implementation, and running of the CRE management system and its alignment to corporates' context and business needs. Connected line diagrams illustrate how "best fit" CREMs can look like.Originality/value – First study takes a holistic view on the organization of the CREM function regarding its alignment with the business strategy and including why different designs are chosen. This can assist to improve the performance of CREM and sets the stage for further research on CREM configurations. Acknowledgements : The authors wish to acknowledge the support of CORPUS SIREO Asset Management Commercial GmbH for their financial support and the challenging discussions regarding this project. The authors thank the anonymous reviewers for their comments and are also grateful to Rianne Appel‐Meulenbroek, TU Eindhoven, and Karen M. Gibler, PhD, Georgia State University, for their valuable feedback.